The Effect of Season and Weather on Physical Activity: A Systematic Review - Hussain Ali Alhafufi et al. (International Journal of Scientific Research and Innovative Studies, 2025)
Physical activity (PA) is a cornerstone of public health, yet participation is not constant year-round. A substantial body of evidence indicates that season and specific meteorological conditions (weather) are significant environmental determinants of PA behavior. This review synthesizes current literature on how these factors influence PA across populations, settings, and activity domains. Findings consistently demonstrate a marked seasonal pattern, with PA levels highest in late spring and summer and lowest in autumn and winter, particularly in temperate and polar climates. Key weather variables impacting PA include temperature (following an inverted U-shaped relationship), precipitation, daylight hours, wind speed, and humidity. The magnitude of effect varies by age, activity type (e.g., walking declines more than gym use), geographical location, and climate zone. Interventions such as seasonal programming, weather-protected infrastructure, and behavioral strategies are crucial to mitigate these effects and promote year-round activity. Understanding these environmental influences is essential for public health surveillance, urban planning, and the design of effective, context-specific PA promotion strategies. Keywords: Physical activity, Seasonality, Weather, Temperature, Precipitation, Built environment, Public health. Received Date: October 20, 2024 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/528